A Single Electrochemical Probe Used for Analysis of Multiple Nucleic Acid Sequences. Issue 3 (15th November 2016) - Mills, Dawn M.; Calvo‐Marzal, Percy; Pinzon, Jeffer M.; Armas, Stephanie; Kolpashchikov, Dmitry M.; Chumbimuni‐Torres, Karin Y.
Abstract: Electrochemical hybridization sensors have been explored extensively for analysis of specific nucleic acids. However, commercialization of the platform is hindered by the need for attachment of separate oligonucleotide probes complementary to a RNA or DNA target to an electrode's surface. Here we demonstrate that a single probe can be used to analyze several nucleic acid targets with high selectivity and low cost. The universal electrochemical four‐way junction (4J)‐forming (UE4J) sensor consists of a universal DNA stem‐loop (USL) probe attached to the electrode's surface and two adaptor strands (m and f) which hybridize to the USL probe and the analyte to form a 4J associate. The m adaptor strand was conjugated with a methylene blue redox marker for signal ON sensing and monitored using square wave voltammetry. We demonstrated that a single sensor can be used for detection of several different DNA/RNA sequences and can be regenerated in 30 seconds by a simple water rinse. The UE4J sensor enables a high selectivity by recognition of a single base substitution, even at room temperature. The UE4J sensor opens a venue for a re‐useable universal platform that can be adopted at low cost for the analysis of DNA or RNA targets. Abstract :